Pemetaan Lokasi Rawan Tindakan Pencurian Sepeda Motor Di Kota Palu Berbasis Sistem Informasi Geografis - Agus Mifta; Widyastuti; Rahmawati; Rifai Mardin (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
Motorcycle theft cases in Palu City often occur in densely populated areas, such as shopping centers, parking areas, residential areas, and boarding houses. This problem is exacerbated by weak supervision in vulnerable areas and the minimal use of GIS with cluster analysis. This study aims to map areas prone to motor vehicle theft (curanmor) in Palu City through the use of Geographic Information Systems (GIS). The methods used include Kernel Density analysis to identify the density of motorcycle theft incidents, cluster analysis to group areas based on vulnerability levels, and overlay techniques are used to obtain a more accurate and informative map of areas prone to motorcycle theft in Palu City. The results of the analysis divide areas into three levels of vulnerability, namely low (score 1–3), medium (score 4–6), and high (score 7–9). Areas with a very high level of vulnerability (red zone) are concentrated in the city center, namely the districts of West Palu, East Palu, South Palu, and parts of Tatanga District. The moderate-risk zone (yellow zone) is located in the transitional area, including parts of North Palu and Mantikulore Districts. The safe zone (green zone) covers outlying areas such as Tawaeli and Ulujadi Districts, and most of Mantikulore. The research findings can serve as a reference for the police and local government in developing strategies for preventing and controlling crime in Palu City.